PENGARUH PROFESIONALISME, KOMPETENSI, PENGALAMAN AUDITOR SERTA ETIKA PROFESI TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS (Studi Empiris pada Kantor Akuntan Publik di Pekanbaru dan Batam) - Septiani Muthiah; Anugerah Rita; Susilatri Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The purpose of this study is to examine the influence professionalism,competence, and experience of auditor and professional ethics on the materialitylevel judgment. The population of this study are auditors who worked on thePublic Accounting Firms (KAP) and listed on the Directory Indonesian Instituteof Certified Public Accountants (IAPI) 2018 in Pekanbaru and Batam. Thesamples of the study are all firms were selected by purposive sampling method.Based on the criteria, 45 auditor’s who worked on 14 KAP were chosen as thesamples of this study. This study used multiple linear regression analysis to testwhether the independent variables affect the dependent variable. Data analysisfor hypothesis test was done with Statistical Package for the Social Sciences(SPSS) ver. 24. Results of regression testing (t-test) showed that theprofessionalism, competence, experience of auditor, and professional ethicsrespectively have a significant effect on the materiality level judgment on PublicAccounting Firm (KAP) in Pekanbaru and Batam. The result of Adjusted RSquare (R2) of 0,781 gives the sense that the rate of 78,1% materialityconsiderations can be explained by the professionalism, competence, experienceof auditor and professional ethics while 21,9% can be explained by othervariables.Keywords : Professionalism, Competence, Experience, Professional Ethics andMateriality level Judgment